Drinking water quality and treatment practices in Pabal, India - Mukadam, Aisha (Cranfield University, 2009)
The drought prone, rural village of Pabal is an example of improved access to water through a piped water system, however at times the villagers are also recipients of a poor water quality supply. Prevailing illnesses of diarrhoea and gastro-intestinal diseases, especially during the monsoons result in 40-50 % of villager‟s income being spent on medical bills. This research project provided by Engineers Without Borders – UK and EngINdia aims to form an investigative study into the current water quality and treatment methods in Pabal. This was achieved by analysing water samples using the DelAgua Water Testing Kit for microbial pathogens (faecal origins) at different points in their distribution system as well as carrying out a social survey through 22 questionnaires and a few target interviews. Results showed the reservoir water source to be highly contaminated but chlorination at the storage tank removed all traces of thermotolerant faecal coliforms. However all consumer points were also found to be contaminated as well as at the borehole hand-pump. Qualitative data collected through observations, sanitary surveys and the questionnaires provided possible reasons for contamination. The pipeline is in disrepair through lack of maintenance, pollutants and effluence (human and animal) are leached into groundwater and pipe supplies, as there are also no drainage or refuse systems in the village. Most villagers are aware and practice basic health, sanitation and water treatment however some only treat once they fall ill. Water treatment is essential in Pabal at all times and should be implemented at a cost-effective household level. The villager‟s health may be safe guarded by utilising traditional methods such as cloth filtering, copper pot storage (anti-bacterial properties) in addition to chlorination. Further education and future water treatment designs based on biosand and UV filtering can be produced locally via the community involving educational centre Vigyan Ashram.
Keywords: drought; piped water system; poor water quality; Engineers Without Borders; EngINdia; DelAgua Water Testing